Output Characteristics of Graphene Field Effect Transistors - V. N. Mishchenka (Приборы и методы измерений, 2020)
The use of graphene, which has high mobility of charge carriers, high thermal conductivity and a number of other positive properties, is promising for the creation of new semiconductor devices with good output characteristics. The aim was to simulate the output characteristics of field effect transistors containing graphene using the Monte-Carlo method and the Poisson equation.Two semiconductor structures in which a single layer (or monolayer) of graphene is placed on a substrate formed from 6H-SiC silicon carbide material are considered. The peculiarity of the first of them is that the contact areas of drain and source were completely located on the graphene layer, the length of which along the longitudinal coordinate was equal to the length of the substrate. The second structure differed in that the length of the graphene layer was shortened and the drain and source areas were partly located on the graphene layer and partly on the substrate.The main output characteristics of field-effect transistors based on the two semiconductor structures considered were obtained by modeling. The modeling was performed using the statistical Monte Carlo method. To perform the simulation, a computational algorithm was developed and a program of numerical simulation using the Monte-Carlo method in three-dimensional space using the Poisson equation was compiled and debugged.The results of the studies show that the development of field-effect transistors using graphene layers can improve the output characteristics – to increase the output current and transconductance, as well as the limit frequency of semiconductor structures in high frequency ranges.